PENGEMASAN TARI RAPA’I GELENG DALAM BENTUK MODUL UNTUK SISWA KELAS XI SEKOLAH MENENGAH ATAS - Hartati Dwi Lestari Marbun; Yusnizar - Heniwaty (Universitas Negeri Medan, 2021)
ABSTRACT - The Rapa'i Geleng dance module is the result of research that has been carried out for teaching materials in Class XI Atasa Middle School. In this study using the theory of Cahyorini and Rusfian (2011: 28):